1999
DOI: 10.1161/01.hyp.33.1.429
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric Vasodilation Mediated by Endothelial Anandamide Receptors

Abstract: Abstract-Cannabinoids, including the endogenous ligand anandamide (arachidonyl ethanolamide), elicit pronounced hypotension in rats via activation of peripherally located CB1 cannabinoid receptors, which have been also implicated in endotoxin (lipopolysaccharide [LPS])-induced hypotension. The present study was designed to test the role of vascular CB1 receptors in cannabinoid-and endotoxin-induced mesenteric vasodilation. In the isolated, buffer-perfused rat mesenteric arterial bed precontracted with phenylep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
209
3
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 237 publications
(227 citation statements)
references
References 38 publications
12
209
3
3
Order By: Relevance
“…The increase in K ϩ current by abn-cbd was unaffected by relevant concentrations of SR141716 or SR144528, which argues against the involvement of CB 1 and CB 2 receptors, respectively. This is further supported by the lack of effect on K ϩ currents of HU-210, a potent CB 1 /CB 2 receptor agonist, which is devoid of mesenteric vasodilator activity (11). On the other hand, the abn-cbd-induced increase in K ϩ current was effectively inhibited by O-1918, a structural analog of cannabidiol, which produced no effect by itself.…”
Section: Discussionmentioning
confidence: 90%
“…The increase in K ϩ current by abn-cbd was unaffected by relevant concentrations of SR141716 or SR144528, which argues against the involvement of CB 1 and CB 2 receptors, respectively. This is further supported by the lack of effect on K ϩ currents of HU-210, a potent CB 1 /CB 2 receptor agonist, which is devoid of mesenteric vasodilator activity (11). On the other hand, the abn-cbd-induced increase in K ϩ current was effectively inhibited by O-1918, a structural analog of cannabidiol, which produced no effect by itself.…”
Section: Discussionmentioning
confidence: 90%
“…A more detailed overview of in vitro effects of anandamide can be found in the following reviews Ho¨gestatt & Zygmunt, 2002;Randall et al, 2002). Some studies have implicated the endothelium in relaxant responses to anandamide (Pratt et al, 1998;Chaytor et al, 1999;Wagner et al, 1999), with the release of prostanoids (Ellis et al, 1995;Fleming et al, 1999), nitric oxide (Deutsch et al, 1997) or endothelial-derived hyperpolarising factor (EDHF) (Chaytor et al, 1999). Some, but not all, studies have reported that anandamide acts through the stimulation of cannabinoid CB 1 receptors, although the intracellular pathway(s) coupling to vasodilatation have not been clearly identified (White & Hiley, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Marijuana, one of the most widely abused substances (1), mediates many of its psychotropic effects by targeting CB 1 receptors in the central nervous system, but studies with CB 1 and CB 2 knock-out mice indicate that the complex pharmacological properties on pain, mood, and memory exhibited by exogenous cannabinoids and the endogenous arachidonic acidbased endo-cannabinoids, including anandamide and 2-arachidonoylglycerol (2-AG), are not fully explained by their activation of CB 1 and CB 2 (2)(3)(4). The CB 1 and CB 2 receptors are 44% identical and signal through G i/o -mediated pathways.…”
mentioning
confidence: 99%